The Effect of ChatGPT-based Constructivist Learning Model on Observation Report Text Writing Skills - Yanthi, Erlina Yuli; Elmustian, Elmustian; Charlina, Charlina (JOLLT Journal of Languages and Language Teaching, 2024)
The importance of observation report text writing skills among vocational students cannot be underestimated, as it is a basic competency that supports the development of their academic literacy. However, at SMK Negeri 2 Pekanbaru, several obstacles were found such as low student motivation and lack of time for effective learning, which hindered the mastery of observation report text writing skills. This study aims to explore the effect of ChatGPT-based Constructivist Learning model in improving observation report text writing skills. Using mixed methods with sequential explanatory design, this study involved 68 students who were divided into experimental and control groups. The results showed that the ChatGPT-based Constructivist Learning model significantly improved the skill of writing observation report text compared to the conventional method. Qualitative data analysis also supported the quantitative findings that students and teachers faced challenges in digital literacy such as difficulties in understanding the user interface or how to interpret the feedback provided. However, this technology has great potential to improve writing skills if implemented well. This study concludes that the integration of ChatGPT-based Constructivist Learning model in learning can improve observation report text writing skills, although habituation in utilizing digital literacy is needed so that it can be implemented effectively and continuously.